Analytical studies of temperature distribution of workpiece in electric discharge machining using semi analytical electro thermal model. (2015) - Mishra, Abhishek; Bhattacharya, Sujay; Datta, Debabrata; Dey, Gautam Kumar
EDM is a non-conventional thermo electric process which erodes material from the workpiece by a series of discrete sparks between the tool and workpiece immersed in a dielectric medium. This discharge occurs in a voltage gap between the electrode and workpiece. Several researchers have carried out their expertise on EDM by numerical modelling as wells as by experimental investigations on various materials in terms of the material removal rate. However, due to complex nature of EDM process the outcome of all those investigations points out 'a lack of understanding from the point of the quantification of the material removal rate'. In view of this, authors have presented a semi analytical approach to model the practical behaviour of EDM. Semi analytical approach is based on the integral transformation method and the numerical evaluation of the integral by Monte Carlo simulation. Computations related to this task are carried out by a computer code 'FOHMON' developed in house by authors. The results obtained are in good agreement with the numerical output that has been presented in the published papers.